Technical Guide: Systems-based approach to understanding, steering and guiding change in Aquatic foods - Manyise, Timothy; Rossignoli, Cristiano; Dentoni, Domenico (WorldFish, 2024)
This guide provides a practical framework for project managers and practitioners to understand and address the complexities of agrifood systems, including aquatic foods. Traditional approaches, like linear Theory of Change (TOC) models, often overlook the intricate relationships and non-linear dynamics within these systems, potentially leading to incomplete assessments of project impacts. The systems-based Theory of Change (STOC) framework addresses these gaps through a four-stage process: identifying challenges within the system, mapping the roles and connections of key actors, envisioning how innovations can drive positive change, and defining stakeholder roles for effective system transformation. By involving stakeholders in a participatory process, this approach fosters collaboration, builds ownership, and ensures that interventions are better aligned with real-world dynamics. The guide complements conventional methods by incorporating systems thinking and mapping, enabling a deeper understanding of both immediate and long-term impacts. Ultimately, it equips users with strategies to design and implement interventions that balance ecological, economic, and social goals, ensuring sustainable and meaningful improvements in agrifood systems.